PENINGKATAN KETERAMPILAN MENCETAK DENGAN MODEL PEMBELAJARAN LANGSUNG BAGI SISWA KELAS II SEKOLAH DASAR - Amelia, Siska (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The main problem in this research is that the achievement of student learning outcomes in class II SDN 06 Batu Taba Kecamatan Ampek Angkek Kabupaten Agam on learning process in printing skill is still far from expectation. The problem was identifiably caused by teacher who does not provide a gradual  learning process. This study aims at improving learning  process in printing skill in the classroom this improving learning outcomes of printing skill in class II SDN 06 Batu Taba Kecamatan Ampek Angkek Kabupaten Agam.The type of research is a classroom action research. This study uses both quantitative and qualitative approach. The study comprises two cycles consisting of planning activity, implementation of action, observation ang reflection. Data collection was carried out with the observation sheets and the works. The result of study performed can be seen as follows, planning activity in cycle I meeting 1 resulted 75% with good qualification, meeting 2 resulted 85% with very good qualification, and cycle II resulted 93% with excellent qualification. Implementation of action by teacher aspect in cycle I meeting 1 resulted 68% with sufficient qualification, meeting 2 resulted 76% with good qualification, and cycle II resulted 93% with excellent qualification. Mean while, implementation of action by student aspect in cycle I meeting 1 resulted 68% with sufficient qualification, meeting 2 resulted 83% with very good qualification, ang cycle II resulted 90% with excellent qualification. In term of student learning outcomes, cycle I meeting 1 resulted 69, meeting 2 resulted 77 and cycle II resulted 82. It is concluded from this research that direct learning model can further improve student’s printing skill learning in class II SDN 06 batu Taba.   Kata Kunci : pembelajaran keterampilan; keterampilan mencetak; model pembelajaran langsung